Soccer: Detailed analysis of played passes in the UEFA Euro 2012 - Mitschke, C.; Milani, T. L. (International Journal of Sports Science and Coaching, 2014)
Many studies investigate kinematic and kinetic aspects of instep and inside soccer kicks to understand these techniques. However, there are currently no studies which show how often these techniques are used in a soccer match. Therefore, soccer games of the UEFA EURO 2012 in the Ukraine and Poland were studied to close this gap. The focus was on which part of the foot or body was used to pass the ball. Length and height of the passes, accuracy, starting position of the pass on field and the change of all these statistics during the whole match were investigated. From all 28271 analysed passes, 59.6% were played in different forms using the inside of the foot, 14.6% with the inner instep, 9.1% with the instep and 16.7% with other body parts, like the outside of the foot, the toes or head.